PRECONCEPTION AND ANTENATAL FOLATE SUPPLEMENTATION INWOMEN WITH PREEXISTING DIABETES - Sidra Anwar; Saniya Umer Draz; Atif Munir; Afshan Ambreen (Baqai Journal of Health Sciences)
Objectives: The aim of this survey is to evaluate the awareness, understanding, and use of folate in clinical practice.